Incidence of Vibrio parahaemolyticus in fisli products marketed in Cochin - Sanjeev, S; Stephen, Jose (Indian Journal of Fisheries, 2011)
Because of world-wide distribution of Vibrio parahaemolyticus in seawater and brackishwater it is extremely difficult to prevent the occurrence of this organism in raw sea foods (Karunasagar et al. 1984). However, measures to control its multiplication in seafood and to prevent recontamination of cooked foods are needed (Liston 1974, Sakazaki et al. 1979).